Retrospective: A Reconfigurable Fabric for Accelerating Large-Scale Datacenter Services - Putnam, Andrew; Caulfield, Adrian; Chung, Eric; Adams, Logan; Constantinides, Kypros; Demme, John; Firestone, Daniel; Heil, Stephen; Humphrey, Matt; Lo, Daniel; Massengill, Todd; Papamichael, Michael; et al. (2023)
An invited author retrospective on “A reconfigurable fabric for accelerating large-scale datacenter services”, the original Project Catapult paper published at ISCA 2014. Included in the ISCA@50 25-Year Retrospective: 1996-2020.